Efforts to Protect Victims of Rape Crime: Law and Society Study (Universitas Negeri Semarang, 2022)
Victims of rape often do not get adequate rights and legal protection. In many cases of rape, the law is not able to fully accommodate the rights of the victim, the law is only limited to fulfilling the desire to punish the perpetrator. The complexity of the legal process usually makes victims prefer the peaceful path. Even though the injuries received by the victim have a serious impact even for the future of the victim. Moreover, many rape cases have reached court but the perpetrators have not been sentenced to the maximum penalty as stated in the Criminal Code. This study is intended to analyze and examine the victim of rape protection in the context of law and society. The study analyzes and compares some related laws concerning to victim protection, women protection, child protection, and human right protection in national context of Indonesia.